Residual force enhancement decreases when scaling from the single muscle fiber to joint level in humans - Avery Hinks; Kaitlyn B.E. Jacob; Makenna A. Patterson; Benjamin E. Dalton; Geoffrey A. Power (Journal of Sport and Health Science)
Background: Residual force enhancement (rFE), defined as increased isometric force following active lengthening compared to a fixed-end isometric contraction at the same muscle length and level of activation, is present across all scales of muscle. While rFE is always present at the cellular level, often rFE “non-responders” are observed during joint-level voluntary contractions. Methods: We compared rFE between the joint level and single fiber level (vastus lateralis biopsies) in 16 young males. In vivo voluntary knee-extensor rFE was measured by comparing steady-state isometric torque between a stretch-hold (maximal activation at 150°, stretch to 70°, hold) and a fixed-end isometric contraction, with ultrasonographic recording of vastus lateralis fascicle length (FL). Fixed-end contractions were performed at 67.5°, 70.0°, 72.5°, and 75.0°; the joint angle that most closely matched FL of the stretch-hold contraction's isometric steady-state was used to calculate rFE. The starting and ending FLs of the stretch-hold contraction were expressed as % optimal FL, determined via torque-angle relationship. Results: In single fiber experiments, the starting and ending fiber lengths were matched relative to optimal length determined from in vivo testing, yielding an average sarcomere excursion of ∼2.2–3.4 µm. There was a greater magnitude of rFE at the single fiber (∼20%) than joint level (∼5%) (p = 0.004), with “non-responders” only observed at the joint level. Conclusion: By comparing rFE across scales within the same participants, we show the development of the rFE non-responder phenomenon is upstream of rFE's cellular mechanisms, with rFE only lost rather than gained when scaling from single fibers to the joint level.